INVESTIGATION OF SHEAR STRENGTH PARAMETERS AND EFFECT OF DIFFERENT COMPACTIVE EFFORT ON LATERITIC SOIL STABILIZED WITH COCONUT HUSK ASH AND LIME (Nigerian Journal of Technology, 2017)
This paper presented the results of the shear strength parameters and compaction characteristics of lateritic soil stabilized with a combination of Lime and Coconut husk ash (CHA) in various percentages using two compaction methods namely; British standard heavy (BSH) and British standard light(BSL). Undrained triaxial test was conducted to determine shear strength parameters of the stabilized soil with confining pressures of 69kN/m2, 138kN/m2 and 276kN/m2, after preliminary tests had been carried out to determine index properties of the soil. The test was conducted on a mixture of natural soil with 4%lime, which gave least plasticity index and percentages of CHA from 0-12% by dry weight of soil. The BSL and BSH were applied on mixture of soil + 4% lime + percentages of CHA ranging from 4-20% by dry weight of soil. The most plausible improvement in maximum dry density was obtained by adding 4% lime + 12% CHA and 4% lime + 16% CHA using BSH and BSL respectively. The results also show significant improvement in angle of internal friction and cohesion of the soil at 6% and 8%CHA addition respectively.http://dx.doi.org/10.4314/njt.v36i4.4